PENGELOLAAN IKLAN LAYANAN MASYARAKAT “JAGA PASOKAN AIR” OLEH HUMAS PDAM TIRTA PAKUAN KOTA BOGOR - Aat Ruchiat Nugraha -; Raden Adi Pratama Putra (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2021)
On July 24, 2019, the Public Relations of the Bogor Municipal Water Supply Company or publicly known as PDAM in Bogor City planned on making a public video advertising program for the first time with